Engineering thermally and electrically conductive biodegradable polymer nanocomposites. (15th May 2020) - Guo, Yichen; Zuo, Xianghao; Xue, Yuan; Tang, Jinghan; Gouzman, Michael; Fang, Yiwei; Zhou, Yuchen; Wang, Likun; Yu, Yingjie; Rafailovich, Miriam H.
Abstract: There is an urgent demand for producing biodegradable polymer based composites with good thermal and/or electrical conductivity to mitigate the plastic pollution introduced by electronic waste. Here, we have designed and engineered a mechanically strong, melt processable, biodegradable polymer based nanocomposite with excellent thermal and electrical conductivity using filler dispersion principle and the work of adhesion ( W a ) as guides. In the design, graphene nano-platelets (GNPs) were dispersed into a highly ductile biodegradable polymer - poly (butylene adipate-co-butylene terephthalate) (PBAT). Blending with another biodegradable polymer, poly (lactic acid) (PLA) that has low affinity to GNPs, confined the dispersion of GNPs within PBAT matrix, thereby facilitating the formation of a percolated network. As a result, high thermal conductivity ( 3.15 W / m ⋅ K ) and electrical conductivity ( 338 S / m ) were achieved for the nanocomposite at 40 wt% of GNPs loading, and the mechanical performance remained strong even at such filler loading due to the strong interaction between GNPs and PBAT. This study provides a new strategy for effectively producing high thermally and/or electrically conductive polymer nanocomposites. Graphical abstract: Image 1